Description Students' Misconceptions about the Concept of Motion in Sambas: Post Covid-19 - Sudirman, Sudirman; Andriani, Riza; Widya, Widya (Journal of Natural Science and Integration, 2023)
This study aims to provide an overview of the misconceptions of 10th-grade high school students in the Sambas district on the concept of motion during a pandemic which is an evaluation of the teaching and learning process of physics during the pandemic (Covid-19). The method used in this study is a survey method with descriptive data analysis with the subject or sample in this study of as many as 223 10th-grade students, consisting of 4 schools with cluster sampling. Based on the data analysis, it can be concluded that the students' misconceptions are still experiencing confusion. If two objects have the same position, they should have the same velocity; and if the two objects have the same velocity, the student assumed that these two objects must have the same acceleration or vice versa. However, students are able to distinguish which ones are scalar quantities and which are vector quantities. As for impetus material, students assume that if an object has a motion, it must have a force acting upon this object. This is a contradiction with newton's first law. Also, it is believed that if the object moves in a circular path, a circular (impetus) force tends to move this object in its path. The highest misconception is in the concept of kinematic about velocity-position and concept of impetus. There is no different in student misconception before and after pandemic covid-19 so that in the future it still needs to improve physisc learning process and physics teacher competence to prevention student misconception.Keywords: misconception, motion, post-covid19